An alternative technique for hollowing maxillary complete denture - Suryakant C Deogade; Aditi Patel; Sneha S Mantri (Wolters Kluwer Medknow Publications, 2016)
Extreme resorption of edentulous maxilla may cause difficulty during fabrication of a maxillary complete denture. Increased inter-ridge distance often creates a clinical problem due to heavy-weighted maxillary prosthesis. This article elaborates an alternative approach for hollowing a maxillary complete denture. It utilizes a clear template of the trial denture facilitating the creation of a gelatin cavity form. This hollowing ensures the even thickness of both denture base resins for structural integrity and reduces the heaviness of the denture.